2007
DOI: 10.1371/journal.pone.0000917
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection and Promiscuous Recombination of Multiple Genotypes of an RNA Virus within a Single Host Generate Extensive Diversity

Abstract: Recombination and reassortment of viral genomes are major processes contributing to the creation of new, emerging viruses. These processes are especially significant in long-term persistent infections where multiple viral genotypes co-replicate in a single host, generating abundant genotypic variants, some of which may possess novel host-colonizing and pathogenicity traits. In some plants, successive vegetative propagation of infected tissues and introduction of new genotypes of a virus by vector transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…This suggests that along with some VT-like genotypes within the Star Ruby GFMS12 plant, some are likely to be recombinants between the B165-or T30-like genotypes in the 5' end and VT-like genotypes in the 3' end. A previous study found that a large number of genetic variants were generated by recombination between major genotypes [24]. Potentially cv.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that along with some VT-like genotypes within the Star Ruby GFMS12 plant, some are likely to be recombinants between the B165-or T30-like genotypes in the 5' end and VT-like genotypes in the 3' end. A previous study found that a large number of genetic variants were generated by recombination between major genotypes [24]. Potentially cv.…”
Section: Discussionmentioning
confidence: 99%
“…Proportionally, the amount of genetic variability produced after a single recombination event is larger than that produced by single point mutations. Although the importance of recombination was underappreciated in early studies of virus genome evolution, it is now recognized as a widespread phenomenon among positive-strand RNA viruses in animals (Grassly & Holmes, 1997;Holmes et al, 1999;Wilson et al, 1988) and plants (Nagy & Bujarski, 1993;Revers et al, 1996;Aranda et al, 1997;Olsthoorn et al, 2002;Bousalem et al, 2003;Cheng & Nagy, 2003;Moreno et al, 2004;Tan et al, 2004;Bonnet et al, 2005;Urbanowicz et al, 2005;Chare & Holmes, 2006;Weng et al, 2007), as well as in retroviruses such as human immunodeficiency virus type 1 Prljic et al, 2004;Althaus & Bonhoeffer, 2005;Galetto & Negroni, 2005), although it is a rare or even non-existent phenomenon among negativestrand viruses (Chare et al, 2003). There are several mechanisms by which RNA recombination may take place, the most common of which is homologous recombination (Lai, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the term homologous refers not only to the presence of sequence homology between both parental RNAs but also the necessity of homologous and comparable sites in both parental molecules for the crossovers to take place (Lai, 1992). Aberrant homologous and non-homologous recombinations are less frequent in nature (Lai, 1992).Amongst positive-strand plant RNA viruses, homologous recombination has been reported in vivo and in vitro during mixed infections (Bousalem et al, 2003;Cheng & Nagy, 2003;Moreno et al, 2004;Tan et al, 2004;Bonnet et al, 2005;Urbanowicz et al, 2005;Weng et al, 2007). Focusing on the family Bromoviridae, reports include recombination events in members of the genera Cucumovirus (Férnandez-Cuartero et al, 1994;Fraile et al, 1997;Roossinck et al, 1999;Chen et al, 2002;Bonnet et al, 2005) and Bromovirus (Bujarski & Kaesberg 1986;Allison et al, 1990), as well as between viruses belonging to different genera (de Wispelaere et al, 2005).…”
mentioning
confidence: 99%
“…Actually, the ratio between non-synonymous and synonymous substitutions assessed for CTV coding regions was below the value 1, thus suggesting selective pressure for amino acid conservation [40]. In addition, analysis of the CTV genomic and D-RNAs sequences indicate homologous and non-homologous recombination events among different genotypes [30,32,41,42,43], possibly as a result of mixed infections on trees that are recurrently inoculated by aphid transmission.…”
Section: Citrus Tristeza Virus Sequence Diversitymentioning
confidence: 99%